2011
DOI: 10.26719/2011.17.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Profile of drug users in Karachi city, Pakistan

Abstract: Drug use has been identified as a major public health issue in Pakistan. A descriptive questionnaire survey in Karachi city was made to identify the socioeconomic profile and beliefs and practices of 500 drug users. The most commonly used drugs were cocaine (19.0%) and crack-cocaine (15.0%), followed by amphetamines (11.0%), alcohol, caffeine, barbiturates and benzodiazepines (10.0% each). Key psychological factors leading to drug use were problems with parental or marital relations or break-up of a relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
3
16
1
1
Order By: Relevance
“…Studies from Pakistan [5], [6] and India [8] have reported similar observations in this regard. A study from Ahmadabad,India [9] observed 46% patients to be below 20 years of age.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Studies from Pakistan [5], [6] and India [8] have reported similar observations in this regard. A study from Ahmadabad,India [9] observed 46% patients to be below 20 years of age.…”
Section: Discussionsupporting
confidence: 68%
“…None of the patients in our study were unemployed prior to getting admitted to the centre and nearly half of them (48.2%) were involved in skilled work. In Karachi, Pakistan [6] 29.6% patients were unemployed; whereas in Chennai, India [10] 31.7% were unemployed. A very small number of patients in our study (3.6%) were either divorced or separated which is significantly lower to that reported in a study from Singapore [7] where 22.3% patients were divorced or separated.…”
Section: Discussionmentioning
confidence: 99%
“…In Karachi, Pakistan 29.6% patients were unemployed; whereas in Chennai, India 31.7% were unemployed. 19,20 A very small number of patients in our study (4.6%) were either divorced or separated which is significantly lower to that reported in a study from Naskar NN et al where 22.3% patients were divorced or separated. 21 The presence of substance use in the family seems to be a significant factor in our study when compared to studies from Ahmadabad and Ghaziabad, where family history of substance use was observed in 26% and 24.8% patients respectively.…”
Section: 8contrasting
confidence: 53%
“…Many drug users blamed the origins of their drug use on bad social influences (47.0%) or socioeconomic problems (23.4%). 21 In a survey 31% adolescents reported that their best friends consume drugs out of which 22% themselves were drug abusers 20 which is in agreement with current study but the percentage for friends as protagonist is 50% identified. The percentage value for having best friends who also consume drugs for frequent abusers was very high i.e.…”
Section: Discussionsupporting
confidence: 81%